2009
DOI: 10.1007/s10531-009-9622-6
|View full text |Cite
|
Sign up to set email alerts
|

Structure of vegetation patches in northwestern Patagonia, Argentina

Abstract: Vegetation of arid and semiarid environments has in general a patchy distribution. Our objective was to (a) determine several qualitative and quantitative analytical characteristics of vegetation patches in an arid zone of Patagonia, Argentina, and (b) investigate relationships between them. Annual precipitation in this area was 200 mm during 1999-2005. Eight transects involving ten patches each were studied within a 15 9 15 km area. Mean (±1 SE) values (n = 80) in the vegetation patches were 315 ± 25 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 47 publications
3
18
0
3
Order By: Relevance
“…Based upon the SEM results, shifts in community structure, as measured by the size of and connectivity of gaps between native plants, exert a strong positive effect on the magnitude of B. tectorum invasion. This finding is consistent with growing evidence in semi‐arid and arid ecosystems showing that increases in gap connectivity (Busso & Bonvissuto ; Okin et al . ) and changes in how species abundance is distributed in a community (James et al .…”
Section: Discussionsupporting
confidence: 92%
“…Based upon the SEM results, shifts in community structure, as measured by the size of and connectivity of gaps between native plants, exert a strong positive effect on the magnitude of B. tectorum invasion. This finding is consistent with growing evidence in semi‐arid and arid ecosystems showing that increases in gap connectivity (Busso & Bonvissuto ; Okin et al . ) and changes in how species abundance is distributed in a community (James et al .…”
Section: Discussionsupporting
confidence: 92%
“…They were 1·5 km apart from each other, and have similar physicochemical soil properties at a plant patch scale (all microsites combined: Table II). A preliminary study demonstrated that vegetation patches in the study region had a greatest and smallest diameter of 3·15 ± 0·25 m and 2·07 ± 0·16 m, respectively (Busso and Bonvissuto, 2009b).…”
Section: Methodsmentioning
confidence: 96%
“…Two sites were used to determine if plant patch structure was either similar or different between them. Busso and Bonvissuto (2009b) reported that plant community structure was similar among these two sites, using transects within a 15 × 15 km study area. Structural characteristics of vegetation patches were also similar at a plant patch scale (Table I).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations